The Effect of Creative Content to Increase Brand Awareness: Information Technology-Based Marketing Strategies - Hasna Eliza Ekaputri; Fanny Aulia Nurfadilah; Faizal Rafsanzani; Raeni Dwi Santy (Universitas Komputer Indonesia, 2021)
In present time there so many brands are using information technology-based marketing strategies with social media platforms. Lots of corporate brands are also competing to spread their creativity to create a content that is packaged as attractively as possible, to increase brand awareness. Especially for start-ups company. The purpose of this research is to find out that a resulting content can have the potential to build brand awareness among the wider community, especially in the field of information technology, social media that has an important influence on consumers, in terms of packaging, product reviews, until go viral. Whether the product is in high demand, will indirectly make an increase in sales. The research method used in this research is by qualitative methods of literature studies, by collecting the extent of in- depth information on documents supporting the influence of creative content to increase brand awareness by using information technology-based marketing strategies. The results show that there is a development of almost 50-70% of brand awareness increases when actively creating content, especially by following current trends that are viral but will be packaged again with typical products owned. Because if the content is made interesting enough it can go to the homepage of non-follower users or can be called explore It also aims to find out the efficiency of brand awareness. In the end, this research can provide positive things to prospective business people who want to start and grow their business by increasing brand awareness by using information technology-based marketing strategies through creative content on social media platforms.